Microwave synthesis, crystal structure, antioxidant, and antimicrobial study of new 6-heptyl-5,6-dihydrobenzo[4,5]imidazo[1,2-c]quinazoline compound - Hasan, HA; Abdulmalek, E; Rahman, MBA; Shaari, KB; Yamin, BM; Chan, KW (Springeropen, 2024)
BackgroundAlthough the development of antibiotic and antioxidant manufacturing, the problem of bacterial resistance and food and/or cosmetics oxidation still needs more efforts to design new derivatives which can help to minimize these troubles. Benzimidazo[1,2-c]quinazolines are nitrogen-rich heterocyclic compounds that possess many pharmaceutical properties such as antimicrobial, anticonvulsant, immunoenhancer, and anticancer.ResultsA comparative study between two methods, (microwave-assisted and conventional heating approaches), was performed to synthesise a new quinazoline derivative from 2-(2-aminophenyl)-1H-benzimidazole and octanal to produce 6-heptyl-5,6-dihydrobenzo[4,5]imidazo[1,2-c]quinazoline (OCT). The compound was characterised using FTIR, H-1 and C-13 NMR, DIMS, as well as X-ray crystallography. The most significant peak in the C-13 NMR spectrum is C-7 at 65.5ppm which confirms the cyclisation process. Crystal structure analysis revealed that the molecule grows in the monoclinic crystal system P2(1)/n space group and stabilised by an intermolecular hydrogen bond between the N1-H1A...N3 atoms. The crystal packing analysis showed that the molecule adopts zig-zag one dimensional chains. Fluorescence study of OCT revealed that it produces blue light when expose to UV-light and its' quantum yield equal to 26%. Antioxidant activity, which included DPPH and ABTS(+) assays was also performed and statistical analysis was achieved via a paired T-test using Minitab 16 software with P<0.05. Also, the antimicrobial assay against two Gram-positive, two Gram-negative, and one fungus was screened for these derivatives.ConclusionsUsing microwave to synthesise OCT have drastically reduced reaction time, and increased yield. OCT show good antioxidant activity in one of the tests and moderate antimicrobial activity.